2019
DOI: 10.1270/jsbbs.19060
|View full text |Cite
|
Sign up to set email alerts
|

Four resistance alleles derived from <i>Oryza longistaminata</i> (A. Chev. & Roehrich) against green rice leafhopper, <i>Nephotettix cincticeps</i> (Uhler) identified using novel introgression lines

Abstract: The green rice leafhopper (GRH, Nephotettix cincticeps Uhler) is a serious insect pest of rice (Oryza sativa L.) in temperate regions of Asia. Wild Oryza species are the main source of resistance to insects. The W1413 accession of African wild rice (O. longistaminata A. Chev. & Roehrich) is resistant to GRH. To analyze its resistance, we developed 28 BC 3 F 3 introgression lines carrying W1413 segments in the genetic background of Nipponbare, a susceptible rice cultivar, and evaluated their GRH resistance. Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Recently some resistant varieties of Oryza longistaminata (A. Chev. & Roehrich) against the green leaf-hoppers are reported [26]. Aphids are another group of sap-sucking insects causing huge damage to crop plants.…”
Section: Major Insect Pests To the Crop Plantsmentioning
confidence: 99%
“…Recently some resistant varieties of Oryza longistaminata (A. Chev. & Roehrich) against the green leaf-hoppers are reported [26]. Aphids are another group of sap-sucking insects causing huge damage to crop plants.…”
Section: Major Insect Pests To the Crop Plantsmentioning
confidence: 99%
“…Van Mai et al ( 2015 ) used two independent F 2 populations derived from a cross of ASD7 × Taichung 65 and mapped two QTLs ( qBPH6 and qBPH12 ) for BPH resistance and one QTL ( qGRH5 ) for green rice leafhopper (GRH) resistance. Recently, Thein et al ( 2019 ) identified four major QTLs, namely qGRH2, qGRH4, qGRH5 , and qGRH11 in African wild rice O. longistaminata accession W1413 derived backcross populations, with qGRH2 being a novel QTL for GRH.…”
Section: Insect Resistance Qtls Identified In Major Field Cropsmentioning
confidence: 99%
“…japonica cv. ‘Nipponbare’ × African wild rice O. longistaminata accession W1413 SSR Greenhouse 2L, 4S, 5S and 11L Green rice leafhopper (GRH) Thein et al ( 2019 ) Rice qGRH5 F 2 ASD7 × Taichung 65 SSR ( RM6082 and RM3318 ) NM 4S GRH Van Mai et al ( 2015 ) Rice gm12 F 2:3 KDML105 × MN62M SNP markers ( S2_76222 and S2_419160 ) Greenhouse 2S Asian rice gall midge Leelagud et al ( 2020 ) Rice gm3 RILs TN1 × RP2068-18-3-5 SSR (RM17480 and gm3SSR4 ) Greenhouse 4L Gall midge Sama et al ( 2014 ) Rice Gm8 RILs TN1 × Aganni SSR ( RM22685 and RM22709 ) Greenhouse 8 Gall midge Sama et al ( 2012 ) Rice Gm11t RILs TN1 × CR57-MR1523 SSR ( RM28574 and RM28706 ) Greenhouse 12 Gall midge Himabindu et al ( ...…”
Section: Insect Resistance Qtls Identified In Major Field Cropsmentioning
confidence: 99%
“…Using a set of 90 ILs derived from the cross between Teqing and Yuanjiang common wild rice (YJCWR), five QTLs related to heat response ( qHST1-1 , qHST1-2 , qHST2 , qHST3 , and qHST8 ) in the seedling stage were detected, and O. rufipogon -derived alleles at one locus reduced sensitivity to heat ( Lei et al, 2013 ). QTLs for resistance to biotic stress, such as that imposed by the green rice leafhopper ( Thein et al, 2019 ), rice stripe necrosis virus ( Gutiérrez et al, 2010 ) and rice blast fungus ( Xu et al, 2015 ), were also mapped using ILs carrying wild rice donor fragments in cultivated rice backgrounds.…”
Section: Progress In Using Introgression Lines In Rice Functional Gen...mentioning
confidence: 99%